Improving South African third graders’ reading skills: Lessons learnt from the use of Guided Reading approach - Mohlanhledi P. Makumbila; Charline B. Rowland (South African Journal of Childhood Education, 2016)
This professional development project, known as Literacy Leadership Project, enabled four Foundation Phase teachers in South Africa to implement the Guided Reading approach. Developed by American researchers Fountas and Pinnell (1996), Guided Reading helps elementary students strengthen their phonemic awareness, vocabulary, reading comprehension and fluency in small group activities. Over an 8-month period, lessons learnt came from data collected from this professional development included workshop activities, classroom observations, teachers’ group discussions and students’ artefacts. Results indicated improvement in students’ literacy engagement and motivation because of the use of levelled books, oral reading and group activities